Mapy procesów logistycznych w systemach zarządzania jakością na przykładzie przedsiębiorstw ciepłowniczych - Łobaziewicz, Monika (Mapping of Logistic Processes in Quality Management System, 2009)
The aim of the paper was analyzing and evaluating maps of chosen logistic processes in heat power engineering enterprises located in Lubelskie region in Poland that had implemented quality management systems according to ISO 9001:2001. The results of research show that logistic processes in the enterprises are mainly determined by low requirements. The range of changes which are implemented in the logistic processes takes into account the following criteria: the way of their organization, establishing of interconnections between processes, the way of information- and workflow to make optimal decisions and determine the necessary competences for personnel. Personal experiences of the author allow to suggest that the enterprises should implement MRPII or ERP systems to improve their business activity based on the process management. MRPII or ERP systems operate in real time or on-line, give the wide range of managerial information, create a professional process structure of the business that catches up to power engineering market requirements. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 306-319